Deflationism and the primary truth bearer - Båve, Arvid ; 0000-0001-7570-2697 (Synthese, 2010)
The paper discusses what kind of truth bearer, or truth-ascription, a deflationist should take as primary. I first present number of arguments against a sententialist view. I then present a deflationary theory which takes propositions as primary, and try to show that it deals neatly with a wide range of linguistic data. Next, I consider both the view that there is no primary truth bearer, and the most common account of sentence truth given by deflationists who take propositions as primary, and argue that they both attribute an implausible type of ambiguity to “true”. This can be avoided, however, if truth-ascriptions to sentences are taken as a certain form of pragmatic ellipses. I end by showing how this hypothesis accommodates a number of intuitions involving truth-ascriptions to sentences.